Dehninterventionen im Spannungsfeld historischer Entwicklung, ritualisierter Anwendung, Meisterlehre und Wissenschaft - Eine Bestandsanalyse - Kremer, Berthold (Karlsruher sportwissenschaftliche Beiträge / Institut für Sport und Sportwissenschaft, Karlsruher Institut für Technologie (KIT). Hrsg.: Prof. Dr. Klaus Bös, PD Dr. Michaela Knoll, 2019)
Almost all possible effects of stretching training are operationalized in connection with the extension of the range of motion. In contrast, stress-associated adaptations are rarely discussed. This means that there is a lack of differentiation for stretch training under salutogenic, therapeutic or performance-physiological goals. In the present study frequently asked questions on the methodology of stretching are answered according to a fact check in comparison with relevant specialist areas.